ANALISIS PELAKSANAAN PROGRAM INOVASI “OJEK TB” DALAM RANGKA MENINGKATKAN CAKUPAN CDR TB : Case Detection Rate Tuberculosis Di Wilayah Kerja Puskesmas Malalak Kabupaten Agam Tahun 2022 (Al Dzahab, 2023)
Purpose: This study aims to analyze the implementation of the ojek TB innovation program in order to increase the coverage of TB CDR in the Malalak Health Center working area, Kabupaten Agam in 2022.Design/methodology/approach: This type of research is qualitative research. Data collection techniques using interviews with triangulation analysis.Findings: This research shows that in terms of policy, Puskesmas still do not have a copy of the document containing policies on regional innovation programs, in terms of human resources, it is still not sufficient considering the size of the work area so that additional human resources are needed, in terms of funding, this innovation program has not been supported by adequate funds for the implementation of activities, so that the CDR achievement of the Puskesmas, although it has increased from before the innovation program, still has not reached the program target, from the facilities and infrastructure there is no allocation of special consumables for this innovation program, there is no recording and reporting of materials special consumables for this program, providing information regarding the existence of this innovation program has not been maximally carried out, information is only carried out during group counseling, or through the Puskesmas network, not all “Ojek TB” officers comply with the SOP in carrying out sampling and delivery of samples m, especially in the use of PPE (Personal Protective Equipment), the supervision of this innovation program has not been carried out properly by the Puskesmas, the District Health Office, as well as by other cross-programs in the sub-district.Research implications: This research is expected to provide academic implications, especially in the field of preventing infectious diseases, especially tuberculosis, to the Malalak Health Center which is the object of research. With this research, the institution can find out how the implementation of the "Ojek TB" innovation program in order to increase the coverage of TB CDR at the Malalak Health Center